The Role of Nollywood in a Dying African Traditional Religion and Culture: A Critique of Clash of Native Doctors (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2025)
Nollywood, also known as the Nigerian film industry, is presently one of the most prolific film industries in the world and the most popular in Africa. However, it appears that Nollywood filmmakers, actors and scriptwriters are neglecting their critical role in the creation, development and perpetuation of the religious, cultural and metaphysical identities of the Nigerian people. Instead, they seem to be portraying some false religious and cultural consciousness of the African people, thereby projecting false ontological and epistemic identities of the people. This paper is a philosophical critique of the contribution of Nollywood to the rapid decline of African Traditional Religions (ATRs) and African Traditional Cultures (ATCs), through a content study of Clash of Native Doctors. The paper shows that most Nollywood scriptwriters, filmmakers and actors/actresses contributed to the dying state of ATR and ATC. A specific analysis of the Nollywood film, Clash of Native Doctors shows that ATRs and ATCs are portrayed as blood-seeking or blood-sucking religions and cultures, while Christianity, whose foundation was laid on the crucifixion and blood sacrifice of a supposed innocent man, is portrayed as the perfect religion. This is logically evident in the film’s transformation of Agada (Dibia or a native priest) who did everything to neutralize the negative spiritual machinations of other Dibias, such as Odenjinji, and Ogbaka, against the innocent people of Anioma community from a native priest to a pastor before he conquered and triumphed over the other Dibias. In fact, the paper argues that the true African Dibia is one who intercedes for his fellow citizens and ensures justice in society rather than someone who performs rituals to stop innocent citizens from making progress, as portrayed in the film.